EFEKTIFITAS EKSTRAK DAUN KELOR (Moringa oleifera lam) DALAM MEMPERBAIKI PROFIL SERUM IRON, SATURASI TRANSFERIN, DAN TOTAL IRON BINDING CAPACITY TIKUS PUTIH JANTAN DIET RENDAH ZAT BESI - Diah Hermayanti; Fathiyah Syafitri (Universitas Muhammadiyah Purwokerto, 2020)
Background : Iron deficinecy can cause anemia which affect health and work productivity. Moringa oleifera leaves contain a lot of iron and vitamin C, are thought to increase serum iron levels, transferin saturation, and improve total iron binding capacity.Objectives : To determine the effectiveness of Moringa oleifera lam. leaf extract on serum iron levels, transferin saturation, and total iron binding capacity in white rats (Rattus novergicus strain wistar) given a diet low in iron (Fe).Materials and methods : true experimental research using post test only control group design. The object of theis study was thirty male white mice (Rattus novergicus strain wistar) who were given a low iron diet. The study was divided into negative control group, positive control, treatment groups with a dose of Moringa leaf extract 400 mg/kg BW, 800 mg/kgBW, 1,600 mg/kg/BW, an the ferro fumaras control group (FF) 175 mg/200 BW.Results and discussion : Multivariate manova serum iron 0.001 (p<0.05), TBC 0.19 (P>0.05), and transferin saturation 0.001(p<0.05). In the post Hoc Tukey the mean serum iron and transferin saturation appeared to differ significant in the negative control group with all the other treatment groups, but did not show a significant diffrence beetwen the positive control group, FF Group, and the treatment groups.Conclusion : The adminstration of Moringa oleifera leaf extractwas less significant in improving serum iron levels, transferin saturation, and total iron binding capacity of male white mice induced by a low iron diet.